Konsep Eskatologi Menurut St. Kirill dari Yerusalem - Pananda, Ika Santi; Hendi (Paramathetes : Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract. The doctrine of the End Times (Eschatology) holds a fundamental place in Christian theology, addressing the ultimate destiny of creation and humanity. This subject has generated continuous discussion and diverse interpretations throughout the history of the Church, reflecting varying theological emphases and responses to historical contexts. While interpretations differ on the precise nature and timing of future events, a core tenet for Christians is the belief in the Second Coming of Jesus Christ, marking the culmination of God's redemptive plan. Despite the explicit biblical affirmation that the exact time of this event is known only to God the Father (Mark 13:32), believers are consistently exhorted to live in vigilance and preparedness. This article undertakes a qualitative study utilizing a literature review approach to explore the eschatological concepts presented by Saint Cyril of Jerusalem in his seminal work, the Catechetical Lectures. Drawing primarily from Cyril's own words within these lectures, supplemented by relevant secondary academic literature, the research analyzes and synthesizes his teachings on key eschatological themes such as the Second Coming, the signs preceding it (including the Antichrist), the resurrection of the dead, the universal judgment, and the eternal destinies. The aim is to articulate Cyril's specific contribution to early Christian eschatology as conveyed in a catechetical context and to explore the pastoral implications embedded within his teachings regarding the end times. By focusing on this influential 4th-century Church Father, the study offers insights into the development of orthodox eschatological thought and its enduring relevance for Christian faith and practice. Abstrak. Doktrin tentang Akhir zaman (Eskatologi) merupakan topik pembimbacaraan yang terus berkembang dari masa kemasa. Ada beragam penafsiran yang dipakai seseorang menafsirkan akhir zaman itu seperti apa. Diantaranya ada penafsir yang menafsirkan akhir zaman sebagai penyesaan. Ada juga yang menafsirkan akhir zaman sebagai perkara-perkara akhir atau akhir dari segala sesuatu. Orang Kristen mempercayai akhir zaman sebagai hari kedatang Tuhan Yesus yang kedua kalinya, namun waktunya tidak ada seorang pun yang tahu bahkan Anak dan Malaikat pun tidak tahu hanya Bapa yang tahu. Oleh karena itu orang percaya semestinya berjaga-jaga. Artikel ini ditulis dengan menggunakan metode kualitatif dengan pendekatan studi literatur dan mengumpulkan berbagai data. Data tersebut dijadikan pendukung dari apa yang dikatakan oleh St. Cyrill of Jerusalem . Sumber yang paling utama digunakan dalam penulisan artikel ini adalah buku katekisasi yang di tulis oleh St. Kirill. Artikel ini ditulis dengan berfokus pada pandangan St. Kirill dari Yerusalem tentang akhir dari alam semesta ini.